BIOGRAFI DAN STUDI TOKOH SEJARAH - Sayono, Joko (Universitas Negeri Malang, 2022)
This paper discusses the concept and steps of historical figure studies. The term historical figure has not been widely discussed and used in historical writing. Writing about the life of a figure is often found in biographies, autobiographies, memoirs and festschrift. These writings are considered a form of historical writing. Problems arise when it comes to the rules that must be followed in historical writing. The lives of the people written about in these four types of writing, usually anyone, can be classified as historical figures or not. Historical figures are very substantial to study, because they are one of the important aspects in the context of driving societal change. The thoughts and actions of historical figures in dealing with various situations can be important lessons and inspiration for others to face the present. It is time to develop the study of historical figures more seriously, with the hope that the results will actually be able to provide more concrete inspiration on how to deal with the situations and conditions that occur around life.Tulisan ini membahas tentang konsep dan langkah-langkah studi tokoh sejarah. Terminologi tokoh sejarah (historical figure) belum banyak dibincangkan dan digunakan dalam penulisan sejarah. Penulisan tentang kehidupan seorang tokoh banyak dijumpai dalam biografi, autobiografi, memoir, dan festschrift. Tulisan-tulisan tersebut dianggap sebagai salah satu bentuk tulisan sejarah.Permasalahan muncul ketika dikaitkan dengan kaidah-kaidah yang harus diikuti dalam penulisan sejarah. Kehidupan orang yang ditulis dalam empat jenis penulisan tersebut, biasa siapa saja, bisa tergolong tokoh sejarah atau bukan. Tokoh sejarah sangat subtansial untuk dikaji, karena menjadi salah satu aspek penting dalam konteks penggerak perubahan masyarakat. Pemikiran dan tindakan tokoh sejarah dalam menghadapi berbagai situasi, dapat menjadi pelajaran penting dan inspirasi bagi orang lain untuk menghadapi masa sekarang. Sudah saatnya dikembangkan kajian tentang tokoh sejarah dengan lebih serius, dengan harapan hasilnya akan betul-betul mampu memberikan inspirasi yang lebih kongkrit bagaimana seharusnya menghadapi situasi dan kondisi yang terjadi di sekitar kehidupan